Situation of fruits and vegetables consumption in the dormitory female students based on the theory of planned behavior - Mahnaz Solhi; Mahboubeh Shirzad (Mashhad University of Medical Sciences, 2016)
Background and objective: Non correct nutrition is one of the most important risk factors for cardiovascular disease, hypertension, diabetes, and obesity. The aim of this study was to determine the status of fruits and vegetables consumption in dormitory female students of Tehran University of Medical Sciences based on the theory of planned behavior. Methods: This cross-sectional study was down on 300 female students dormitories of Tehran University of Medical Sciences. Samples were selected by random sampling. Data gathered by a questionnaire with 13 demographic questions, 42 questions about daily consumption of fruits and vegetables, 2 questions of behavioral intention, 15 questions of attitude, 5 questions of subjective norms, 7 questions about perceived behavioral control and 5 questions of enabling factors. Validity and reliability of the questionnaire was determined in a pilot study. Data were analyzed by SPSS software (version16) and using descriptive and analytical statistics tests. Results: 86% of the samples had favorable behavioral intentions, all of them had desirable attitudes. 63 percent of them had favorable subjective norms and 78 percent of them had favorable perceived behavioral control and 84.7 percent of them had favorable enabling factors. There were significant correlations between fruit and vegetable consumption behaviors with the intention, perceived behavioral control and enabling factors based on the correlation co-efficient and leaner regression Tests. Intention, perceived behavioral control and enabling factors were predictors of fruits and vegetables consumption among these students. Conclusion: Intention, perceived behavioral control and enabling factors were important predictors of fruit and vegetable consumption in these students. Paper type: Research Article